Ricardo Was Right: Unless One Can Enforce Productive Behaviour from Rentiers, Sustainable Growth Is Not an Option - While Emerging Asia Succeeded, the West and Latin America Failed, Caught in Their Neo-Liberal Trap . a Tribute to Geoff Harcourt - Palma-Penco, J (TAYLOR & FRANCIS LTD, 2026)
The 1980s neo-liberal reforms led the West - both developed and Latin America - to capitulate to rentiers at the worst possible time, given rapid technological change and evolving world order. Instead of productive flexibilities, they delivered a neo-liberal trap with its growth-retarding trilogy: a market inequality-augmenting, investment-weakening, and productivity growth-retarding scenario. These reforms turned loose the uncreative-destructiveness of a rentier-based accumulation by indiscriminately strengthening rentiers property-rights, which allowed them build an economy and a political settlement - even an ideology - in their own image. In such distorted markets, technological change and international trade could only create market opportunities, but not the necessary compulsions to be taken up. Following Geoff Harcourt s lead, I analyse this returning to the Classics ; in my case, to a broad Ricardian perspective on rents and rentiers. Emerging Asia, meanwhile, was able to take these opportunities by redirecting rentiers income towards socially desirable investment strategies - aimed at demand adapt and supply upgrade their productive strategies. Bretton Woods was a guide. But in the West, as rentiers gained the upper hand, the resulting process of rentierisation - of which financialisation is just one, although leading, aspect - is now proving as toxic for inequality, investment and productivity-growth as it is for our democracy.